Batteries: Solution‐Processed All‐V2O5 Battery (Small 40/2020). Issue 40 (7th October 2020) - Wang, Guolong; Cui, Xiaoqian; Liu, Jiamei; Wang, Yaling; Qiao, Yide; Shi, Xiaowei; Zhang, Yan; Liu, Heguang; Li, Lei
Abstract : In article number 2003816, Lei Li and co‐workers implement a proof‐of‐concept solution‐processed all‐V2 O5 battery with symmetrical electrode structure. The electrodes are prepared via the solution‐processed method, indicated by the river with the boat. V2 O5 works as both cathode and anode. The storage/release charges via Li + intercalation/de‐intercalation in V2 O5 like the balanced mutual transformation between "Yin" and "Yang" of the Chinese traditional "Tai Chi" diagram.